Power quality assessment of a wave energy converter using energy storage - Md Imran Ullah; Johan Forslund; Jessica S. Döhler; Irina Temiz (International Marine Energy Journal)
Wave energy has been an immense area of interest in research and industry in our move toward a sustainable energy production society due to its high energy density and surface area. However, the grid connection of wave energy converters is still one of the major challenges due to the complexity of varying wave resources (amplitude and frequency). Wave energy converter grid integration can lead to several potential challenges, such as voltage fluctuations, harmonics and flicker. Using an energy storage system can help mitigate a few challenges by balancing the grid demand with the wave energy converter power supply. Hence, improving the power quality. This study assesses the power quality of wave energy converters equipped with energy storage against the scenario without any energy storage at different power levels. The power quality in this paper is investigated using total harmonic distortion (THD) of the grid current, dc-link voltage ripple and battery current ripple. The study shows that the addition of a hybrid energy storage system lowers the grid current THD at the point of common coupling (PCC), stabilizes the dc-link voltage ripple and reduces the stress of the battery.